2012
DOI: 10.1590/s0100-69162012000500003
|View full text |Cite
|
Sign up to set email alerts
|

Yield and quality of elephant grass biomass produced in the cerrados region for bioenergy

Abstract: ABSTRACT:The objective of this study was to evaluate the performance of two genotypes of elephant grass, fertilized with and without N, for biomass production for energy use under the edaphoclimatic conditions of the Cerrado. The genotypes Roxo and Paraíso, grown in a field experiment in a Latosol in the Cerrado region were evaluated for biomass yield, nitrogen accumulation, C:N and stem:leaf ratios, fibre, ash and P and K contents and calorific value. The accumulated dry biomass ranged from 30 to 42 Mg ha -1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 12 publications
3
27
0
5
Order By: Relevance
“…Results for GCV in sugarcane stems noted in previous studies were 18.87 MJ kg -1 found by Ripoli et al (1991) and ranged from 14 to 22 MJ kg -1 as described by Quirino et al (2005) for species appropriate for energy production. In addition, the values found in this study are very close to those found in studies of other species used for energy purposes (Queno et al, 2011;Flores et al, 2012).…”
Section: Ash Content and Gross Calorific Value (Gcv)supporting
confidence: 90%
“…Results for GCV in sugarcane stems noted in previous studies were 18.87 MJ kg -1 found by Ripoli et al (1991) and ranged from 14 to 22 MJ kg -1 as described by Quirino et al (2005) for species appropriate for energy production. In addition, the values found in this study are very close to those found in studies of other species used for energy purposes (Queno et al, 2011;Flores et al, 2012).…”
Section: Ash Content and Gross Calorific Value (Gcv)supporting
confidence: 90%
“…Segundo Mello et al (2002) é possível selecionar clones de capim-elefante por meio do DC, objetivando maior PMS. Aproximadamente 72% da biomassa do capim-elefante correspondem ao colmo que possui alto teor de fibra, lignina e outros componentes importantes para uma boa qualidade de biomassa para energia (Flores et al, 2012).…”
Section: Resultsunclassified
“…20-cm-long cuttings were planted at depth of 10 cm, spaced by 20 x 20 cm, totaling 25 cuttings, with one bud each, per plot. This species was chosen for its high biomass production, promoted by the efficient fixation of atmospheric CO 2 (Flores et al, 2012).…”
Section: Methodsmentioning
confidence: 99%